THE ROLE AND PLACE OF THE MYSTERY IN METAPHYSICS OF MAMLEEV’S CHAOSMOS - Honcharov, Semen A. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2020)
The article examines the role and place of the Mystery within the structure of Mamleev’s metaphysics. The author of the article implicates the concept of “chaosmos’’, introduced by James Joyce in the experimental novel “Finnegans Wake”, to the Mamleev’s Universe. This leads to the transformation of the formula “chaos – osmosis – cosmos”, actualized by postmodern discourse, into the formula “Chaos – Osmosis – Cosmos”. Chaos here is Sacred Chaos, being one of the metaphysical manifestations of Eternal Russia. Osmosis appears to be an antinomic Russian life, which combines the incompatible, and sets itself fundamentally impossible tasks. The Сosmos brings us to the tradition of Russian cosmism with its problem of microcosm and macrocosm conformity. The author of the article points out that the all-pervading and unifying element of Mamleev’s chaos is the Mystery. It is one of the five key metathemes of Mamleev’s oeuvre. The particularity of the Mystery is that it provides a link between other metathemes: utrism “I”, Death, the Abyss and Russia. In the plane of utrism “I” the Mystery is seen as the mystery of man (his higher “I”). The Mystery is related to Death by the person’s interest of his own destiny and finiteness. The problem of overcoming death and the passion for eternal life are the central themes that concern almost all the heroes of Mamleev’s novels and short stories. For Mamleev they are the source of values aimed at the human need to achieve a higher “I”. The connection between the Mystery and the Abyss, as well as the connection between the Mystery and Russia are the strongest and the most important for Mamleev. Consideration of these connections prompts the author to conclude that Yuri Mamleev describes such dimensions of the Mystery, which go beyond the categories “unfathomable-to-us” and “unfathomable-in-itself”, introduced by S. Frank. This requires the introduction of new concepts that would bring out the essence of Mamleev’s innovations. The author of the article proposes to consider the Abyss as a “Last Mystery” by the fact it is transcendent to the transcendents themselves, that is it goes beyond the Absolute, as well as to consider Eternal Russia as a Russia-Mystery on the grounds that Mamleev gives it the status of the third metaphysical Beginning, along with the Absolute and the Abyss.